A Analisis Epistemological Obstacles Mahasiswa Memahami Konsep Matriks dalam Hubungannaya dengan Pendidikan Karakter - Mahyudi Yudi; Endaryono Endaryono; Aswin Saputra (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
Epistemological barriers arise due to students' limited knowledge of certain contexts because they do not obtain complete information which will result in students' difficulties in finding relationships and in connecting concepts. Epistemological barriers are closely related to errors and difficulties that occur in abstract mathematical study objects, the mathematical objects in question include concepts, facts, and principles. There are three indicators of epistemological barriers, namely conceptual barriers, procedural barriers and technical operational barriers. This obstacle will be studied by looking at the character of students in learning. The results of the study show that the initial concept of the meaning of rank and the technique of a multiplication matrix becomes an obstacle in understanding the concept of a matrix. Meanwhile, the second learning obstacle is a learning obstacle related to students' understanding of the concept of matrix multiplication with matrices. In terms of its relationship with student learning characters, several characters such as low curiosity, discipline, hard work and fond of reading, become inhibiting factors in learning, especially in understanding mathematical concepts, especially matrix concepts.